The effects of lemon taste on attention, perceived exertion, and affect during a stepping task. (July 2016) - Ritchie, Jason; Braun, Robyn; Basevitch, Itay; Boiangin, Nataniel; Tenenbaum, Gershon
Abstract: Objectives: To better understand the effects of taste cues on delaying the attention shift from an external focus (dissociative) towards an internal focus (associative) as exercise intensity increases. Design: A between subjects' experimental design with random assignment to three groups: taste (lemon-flavored mouth guards), placebo (unflavored mouth guards), or control group (no mouth guards) was used. Participants reported perceived exertion, affect (i.e., pleasantness and arousal), and attention allocation before, during, and after performing a weighted stepping task. Results: Performing the task resulted in a gradual increase of perceived exertion, F (1.87, 74.89) = 63.05, p < .05, η p 2 = .61, along with a shift from dissociative to associative attention, F (2.17, 86.68) = 35.57, p < .05, η p 2 = .47 across all conditions. Additionally, participants reported feeling less pleasant and more aroused after task completion in all conditions. The lemon-flavored mouth guard failed to affect attention, F (4.33, 86.68) = 1.41, p = .23, η p 2 = .07, perceived exertion, F (3.74, 74.86) = .38, p = .81, η p 2 = .02, pleasantness, F (2, 40) = .126, p = .88, η p 2 = .01, and arousal, F (2, 40) = 2.40, p = .10, η p 2 = .10, differently than the other two conditions. Conclusions: The study was one of the first to examine the effects of taste during an exertive task. Despite the non-significant effects of using a lemon-taste mouth guard on various cognitive variables (perception of exertion, attention allocation, pleasantness, and arousal), more scientific effort is needed to explore the effects of other tastes (e.g., sweet, bitter) and delivery methods (e.g., sprays, drops). Highlights: Attention shifted from dissociative to associative as exercise intensity increased. Ratings of perceived exertion increased linearly with time and effort. Taste (lemon flavor) did not significantly delay the attention shift. Taste did not affect ratings of perceived exertion.